2001
DOI: 10.1017/s002531540100340x
|View full text |Cite
|
Sign up to set email alerts
|

Maturity, fecundity and reproductive potential of the European lobster (Homarus gammarus) in Ireland

Abstract: Fecundity and size at maturity of the European lobster Homarus gammarus (Crustacea: Decapoda) was estimated in four coastal regions of Ireland. Egg size increased with carapace length (CL) (egg size=0·9939×ln (CL)−3·0809). The size–fecundity relationship for all coasts combined was (fecundity=0·0044×CL3·1554).  Physiological maturity was assessed using ovary colour, ovary factor, ova size, abdomen width/CL ratio, cement gland activity and moult status as criteria. Size at 50% maturity varied from 92·5 to 96  m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 12 publications
2
50
0
3
Order By: Relevance
“…Egg size increased significantly with maternal body size. This finding is in concordance with previous work conducted on European lobsters in other regions (Tully et al 2001, Jørstad et al 2005, Agnalt et al 2008). In addition, we document that egg size is closely linked to larval size, implying that egg size (measured as DW) is a good approximation of offspring size.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Egg size increased significantly with maternal body size. This finding is in concordance with previous work conducted on European lobsters in other regions (Tully et al 2001, Jørstad et al 2005, Agnalt et al 2008). In addition, we document that egg size is closely linked to larval size, implying that egg size (measured as DW) is a good approximation of offspring size.…”
Section: Discussionsupporting
confidence: 94%
“…In some American lobster Homarus americanus populations, egg size is a function of female size, with larger females producing larger eggs with higher energetic content (Attard & Hudon 1987, Sibert et al 2004. Similarly, in the European lobster Homarus gammarus, both fecundity and egg size increase with maternal size (Tully et al 2001, Agnalt et al 2008. In this species, there is also some evidence that maternal size may have a positive effect on offspring survival, as measured under semi-natural conditions during the early benthic phase (Jørstad et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ennis (1980) has indicated that the inflections and asymptotes needed to establish the size at maturity are not very distinct based on the L C /A W vs. L C graphs. Similarly, Tully et al (2001) was unable to match maturity based on the maturity index (morphometric maturity) with maturity based on ovarian condition for the European lobster (H. gammarus Linnaeus, 1758). Given negative results in this and other studies, we do not recommend that the maturity index based on the morphometry of the abdomen be used to detect the onset of female sexual maturity in lobsters of the genus Homarus.…”
Section: Size At Maturitymentioning
confidence: 99%
“…It has been presented here for Nephrops at southwest Iceland and has also been described for Nephrops in the Celtic Sea (Morizur and Rivoalen, 1982). Also, in the European lobster Homarus gammarus, egg size has been shown to be positively, but only weakly, related to female CL (Lizàrraga-Cubedo et al, 2003;Tully et al, 2001) and similarly in the American lobster H. americanus (Attard and Hudon, 1987;Ouellet and Plante, 2004).…”
Section: Female Maturity Stagesmentioning
confidence: 98%